EARLY INFANT FEEDING AND THE RISK OF TYPE 1 DIABETES : A SYSTEMATIC REVIEW - Stevenie, (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Recent studies indicate that the development of autoimmunity in T-cells develops within the first few years of life; in fact, autoantibodies are normally detectable by age 2 in the majority of cases. Due to this, researchers have been searching for environmental factors that influence early development, with a particular emphasis on the role nutrition plays in these processes. The gap between these results may also indicate the impact of genetic background on an individual's vulnerability to various environmental stimuli. In addition, the majority of these studies focused on the diets of adults, whereas more recent research has emphasized the significance of neonatal feeding practices and early nutrition in the onset of type 1 diabetes. Early nutrition is one of the earliest environmental factors to which a child is exposed. Given that the first signs of cell autoimmunity emerge during the first year of life in many subjects who later present with clinical type 1 diabetes and that the most conspicuous increase in the incidence of type 1 diabetes has been observed among those diagnosed before the age of 5 years, it is likely that the disease process is initiated in the majority of cases during childhood.